2015
DOI: 10.1176/appi.ps.201400342
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mental Health Services by Children Ages Six to 11 With Emotional or Behavioral Difficulties

Abstract: Objective The authors reported use of mental health services among children in the United States between ages six and 11 who were described by their parents as having emotional or behavioral difficulties (EBDs). Methods Using data from the 2010–2012 National Health Interview Survey, the authors estimated the national percentage of children ages six to 11 with serious or minor EBDs (N=2,500) who received treatment for their difficulties, including only mental health services other than medication (psychosocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 59 publications
2
39
2
2
Order By: Relevance
“…A quarter of the children (23.2 %) of the children had experienced a hospitalization in the prior 3 months. Our service utilization findings are similar to a recent national study indicating that 81.8 % of school-age children with a serious EBD were receiving either psychosocial services, medication management, or both (Simon et al 2015). …”
Section: Service Utilizationsupporting
confidence: 88%
“…A quarter of the children (23.2 %) of the children had experienced a hospitalization in the prior 3 months. Our service utilization findings are similar to a recent national study indicating that 81.8 % of school-age children with a serious EBD were receiving either psychosocial services, medication management, or both (Simon et al 2015). …”
Section: Service Utilizationsupporting
confidence: 88%
“…Pediatric clinicians not well trained in assessment of behavioral health conditions might be inclined to overdiagnose patients presenting with emotional distress. However, it is well known that many patients, both pediatric and adult, never seek care for behavioral conditions, and thus these conditions are never diagnosed, 36,37 so the BHC point prevalence that we found may actually underestimate the true point prevalence of BHCs among adolescents in this population. Moreover, in previous studies in this health system that examined primary care provider behaviors and attitudes toward identifying adolescent behavioral health conditions, we have found primary care providers in particular to be cautious about diagnosing psychiatric and SUDs in adolescents.…”
Section: Discussionmentioning
confidence: 68%
“…In the United States, Simon, Pastor, Reuben, Huang, and Goldstrom's study indicated that 5.8% of school-aged children had serious psychiatric disorders, and 17.3% had minor disorders (2015). Among these children, 17.8% were receiving both medication and psychosocial (psychological and rehabilitative) services, 28.8% psychosocial services only, 6.8% medication only, and 46.6% neither medication nor psychosocial services (Simon et al, 2015). Therefore, received treatment services students with SLD in Tehran is not at optimal levels.…”
Section: Discussionmentioning
confidence: 99%